Perceptions on clinical supervision in a private dental college in the Philippines - Colina, Trinette C.
The integration of knowledge from basic sciences to clinical dentistry is an important learning process experienced by dentistry students. The entire process is facilitated by the faculty, officially recognized as the clinical supervisor. This research described faculty and student perceptions regarding clinical supervision in a Philippine dental school. It identified the factors which affect faculty and student perceptions, whether both perceptions are congruent, and explained the similarities and differences. A mixed methods explanatory sequential design was used to explore faculty and student perceptions on clinical supervision. Forty-eight faculty and two hundred ninety-five students (N=343) of a private dental university answered the Maastricht Clinical Teaching Questionnaire (MCTQ) for the Quantitative Phase 1. Survey results showed both faculty and students had positive assessments of clinical supervision, however, their ratings of the domains differed. The faculty had a significantly positive overall assessment than the students, according to the two-sample Kolmogorov-Smirnov test conducted. Two-tailed T-tests revealed that student perceptions were not affected by sex and year level. On the other hand, ANOVA revealed that faculty perceptions were affected by the number of years in teaching, with ‘experts’ having more positive ratings. The Qualitative Phase 2 was conducted to study the observations yielded by Phase 1. Ten faculty and thirty students participated in in-depth interviews and focus group discussions. Analysis of responses using NVivo 12 revealed common themes across respondents: 1ack of time because of high faculty-student ratio affected clinical supervision, lack of improvement in interaction between faculty and fourth-year clinicians due to high expectations affected learning environment, faculty traits may affect student motivations positively or negatively, and variable faculty competence due to the number of years teaching affect competence in clinical supervision. Recommendations include institutionalizing the practice of reflection and feedback on the conduct of clinical supervision in the protocols of the clinical department, incorporation of training in the domains of clinical supervision in the continuing professional development of faculty, and ongoing research on best practices on clinical supervision across departments of the university, and inter-universities, using MCTQ as the common tool to facilitate communication and comparison of results.